Avaliação da toxicidade e atividade antitumoral de nanopartículas de óxido de cério associados ao óxido de zinco - Xavier, Aline Lira (2015)
Nanomedicine is the use of nanomaterials in developing new therapeutic and diagnostic procedures. However, despite the advantages and different applications of nanoparticles, they also have potential toxic effects that should be properly assessed before use. Metal oxides and, in particular, metal oxide nanoparticles have many applications. Among them, cerium oxide nanoparticles and zinc oxide have shown different pharmacological activities, both alone, and in combination with each other. Cancer is a complex genetic disease which is a major public health problem worldwide, one of the leading causes of death in Brazil. This study aimed to evaluate the toxicity and antitumor activity in vivo of cerium oxide nanoparticles and zinc oxide association (NCZ). Initially it was evaluated the acute preclinical toxicity orally with estimated NCZ LD50 above 2000 mg/kg, therefore, the sample is considered to have low toxicity in our experimental conditions. Subsequently it was performed the evaluation of repeated doses toxicity study (28 days) of NCZ by oral route. The treatment resulted in a significant decrease in the consumption of water and feed, significant increase in enzyme activity of ALT and AST, significant decrease of urea, significant increase in the total white blood cell count, significant decrease in thymus index, significantly increased of ambulation and a decrease in time of self-cleaning and withdrawals. The study of acute toxicity by intraperitoneal route, the LD50 of NCZ was estimated at about 300 mg/kg enabling the choice of doses to be used in the study of antitumor activity. NCZ showed significant antitumor activity in Ehrlich ascites carcinoma model (EAC) at doses of 10, 20 and 40 mg/kg, considering the mass, tumor volume and total cell parameters. In the investigation of its mechanism of action was observed that NCZ increased the percentage of cells in sub-G1 phase, decreased microvessel peritoneal vascular, as well promoted an increased in the concentration of IL-1, IL-10, TNF- and IFN-. It was also evaluated the toxicity of NCZ in animals with EAC submitted to antitumor treatment for nine days. It was observed a significant decrease in feed intake, significant increase in ALT activity, significant decrease in serum urea concentration, significant increase in serum creatinine and significant increase in the mean corpuscular hemoglobin. According to the results, we can infer that NCZ has low toxicity and significant antitumor activity in vivo with mechanism of action probably related to interference with the progression of the cell cycle, inducing apoptosis, increased immune response and antiangiogenic action.